09 Teaching Spanish in Albania Before and After the '90 - Anastasi PRODANI; Aida GJINALI; Sandra GJOKA (Association of Social and Educational Innovation, 2014)
In Albania, the teaching of Spanish language at schools dates back to 1979. It began for the first time in the high school of foreign languages "Asim Vokshi", where only one language was taught as a foreign language despite the fact that other languages such as English, Russian, French were offered , too, and in 1979 German and Italian was also included. The introduction of Spanish language in 1979 was inevitable due to the necessity of using Spanish manuals. It is a known fact that Albania before the '90s was an isolated country with a communist regime and finding manuals for learning Spanish language was fairly difficult. It was impossible to find or to select an adequate manual as there was none. There was no market at all for Spanish books. You could not find Spanish manuals neither in the National Library nor in other regional libraries. In such a situation of total lack, the only source was the personal library of some Spanish people, Marxist- Leninist ones, the first professors of Spanish language in Albania during the '70s and the '80s, who were members of the Communist (M-L) Party of Spain and came to Albania to teach Spanish but also to help the communist propaganda for the socialist model built in Albania. The purpose of our paper besides presenting a brief history of Spanish language teaching in Albania is also to bring in focus the examination of Spanish manuals used for more than 30 years, analyzing the manuals before and after the '90s, and to see what was offered then and what is offered today when Spanish is taught not only as a Foreign Language (E / LE), but also as a Content-Based Language.